ANALYSIS OF INTERNAL MIGRATION DETERMINANTS IN INDONESIA - Amprul Khoeri; Hastarini Dwi Atmanti (Universitas Tidar, 2021)
Population issues are a crucial factor in conducting development to achieve people's welfare. Population migration has an impact, either directly or indirectly, on aspects of life such as social, economic, health, and environmental impacts. This study aims to identify the factors that influence the population's decision to conduct internal migration in Indonesia. This study uses secondary data sourced from the Indonesian Household Life Aspect Survey (SAKERTI) or the Indonesian Family Life Survey wave 5 (IFLS-5) or known as IFLS 2014. The data analysis method used is the probit regression model analysis using the version 14 Stata program. The results showed that the variables that significantly influence the population's decision to conduct internal migration in Indonesia are income, work status, education, age, number of family members, marital status, residence ownership status, and agricultural land ownership. Meanwhile, gender variables and public transportation facilities do not affect the population's decision to conduct internal migration in Indonesia.